INFORMATION SYSTEM DESIGN MAP DATA SEARCH IN PT. AMOSEAS INDOENSIA - Suratno Wahidin; Drs. Eko Hadiyanto, MM Drs. Eko Hadiyanto, MM (Jurnal Sistem Informasi, 1997)
Availability of data at the time it takes has to be the key success of the course of anactivity. This also applies to a mining company such as the PT. Amoseas IndonesiaInc.. And to ensure the availability of accurate and timely data, in addition to physicaldata storage capacity is good, then the search data will also play an important role toinfluence the availability of data. Therefore the use of aid programs for data search isalso very important existence.